Prevalence, comorbidities, diagnosis, and treatment of nonallergic rhinitis: real-world comparison with allergic rhinitis - Hye Yung Yum; Eun Kyo Ha; Yoon Ho Shin; Man Yong Han (The Korean Pediatric Society, 2021)
Rhinitis is among the most common respiratory diseases in children. Nonallergic rhinitis, which involves nasal symptoms without evidence of systemic allergic inflammation or infection, is a heterogeneous entity with diverse manifestations and intensities. Nonallergic rhinitis accounts for 16%-89% of the chronic rhinitis cases, affecting 1%-50% (median 10%) of the total pediatric population. The clinical course of nonallergic rhinitis is generally rather mild and less likely to be associated with allergic comorbidities than allergic rhinitis. Here, we aimed to estimate the rate of coexisting comorbidities of nonallergic rhinitis. Nonallergic rhinitis is more prevalent during the first 2 years of life; however, its underestimation for children with atopic tendencies is likely due to low positive rates of specific allergic tests during early childhood. Local allergic rhinitis is a recently noted phenotype with rates similar to those in adults (median, 44%; range, 4%-67%), among patients previously diagnosed with nonallergic rhinitis. Idiopathic rhinitis, a subtype of nonallergic rhinitis, has been poorly studied in children, and its rates are known to be lower than those in adults. The prevalence of nonallergic rhinitis with eosinophilia syndrome is even lower. A correlation between nonallergic rhinitis and pollution has been suggested owing to the recent increase in nonallergic rhinitis rates in highly developing regions such as some Asian countries, but many aspects remain unknown. Conventional treatments include antihistamines, intranasal corticosteroids, and recent treatments include combination of intranasal corticosteroids with azelastin or decongestants. Here we review the prevalence, diagnosis, comorbidities, and treatment recommendations for nonallergic rhinitis versus allergic rhinitis in children.